Optimizing anticoagulation for patients receiving Impella support. Issue 11 (9th November 2021) - Beavers, Craig J.; DiDomenico, Robert J.; Dunn, Steven P.; Cox, Jenna; To, Long; Weeks, Phillip; Trujillo, Toby C.; Jennings, Douglas L.
Abstract: Anticoagulation of patients treated with the Impella percutaneous mechanical circulatory support (MCS) devices is complex and lacks consistency across centers, potentially increasing the risk of complications. In order to optimize safety and efficacy, an expert committee synthesized all available evidence evaluating anticoagulation for patients receiving Impella support in order to provide consensus recommendations for the management of anticoagulation with these devices. The evidence synthesis led to the creation of 42 recommendations to improve anticoagulation management related to the use of the Impella devices. Recommendations address purge solution management, intravenous anticoagulation, monitoring, evaluation and management of heparin‐induced thrombocytopenia (HIT), and management during combination MCS support. The use of a heparinized, dextrose‐containing purge solution is critical for optimal device function, and a bicarbonate‐based purge solution may be an alternative in certain situations. Likewise, intravenous (ie, systemic) anticoagulation with heparin is often necessary, although evidence supporting the optimal assay and target range for monitoring the level of anticoagulation is generally lacking. Patients treated with an Impella MCS device may develop HIT, which is more difficult to evaluate and treat in this setting. Lastly, the use of Impella with extracorporeal membrane oxygenation or for biventricular support creates additional anticoagulation challenges.